Hermeneutika Terjemah Al-Qur’an Era Kolonial: Telaah Kitab Terjemah Al-Qur’an Hidāḥyah al-Raḥmān - Muhammad Fathur Rozaq (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2018)
The process of translating the Koran into local languages has a hermeneutic side that depends on the translator's milieu. This cannot be avoided as a logical consequence of the gradation of God's words into human words. Even the translated book of the Qur'an Hidāya al-Raḥmān by Muhammad Hanbali cannot be separated from the context - in this case colonial - so that this work also becomes an integral part that can be used to add fragments to the picture of the period. The author assumes that the study of this book has its own significance because the translation of the Qur'an has a broader range of verses than the Qur'anic commentary which is only studied by educated circles. This article will reveal the process of writing translation texts written in the pre-independence era. Furthermore, the factors causing the content of the text are arranged in a certain way as an answer or resistance to the problems at that time. Schleiermacher's hermeneutic theory will be used as an approach to understanding the overall picture or number and partial description or phenomenon of the text. From this it was found that the writing of this book was carried out carefully because of the supervision of the colonial government against the text to protect the status quo. Besides that, the nuances of the pensantren and Javanese ethics strongly influenced the writing style of the book.Keywords: Translation, Hidāya al-Raḥmān, colonial, hermeneutics. Proses penerjemahan Al-Qur’an ke dalam bahasa lokal memiliki sisi hermeneutis yang bergantung pada milieu penerjemah. Hal ini tidak dapat dihindari sebagai konsekuensi logis akan gradasi dari kata-kata Tuhan menjadi kata-kata manusia. Pun kitab terjemah Al-Qur’an Hidāyah al-Raḥmān karya Muhammad Hanbali tidak lepas dari konteks –dalam hal ini kolonial– sehingga karya ini juga menjadi bagian integral yang dapat digunakan untuk menambah fragmen gambaran kurun tersebut. Penulis berasumsi bahwa telaah terhadap kitab ini memiliki signifikansi tersendiri karena terjemah Al-Qur’an memiliki jangakauan lebih luas daripada kitab tafsir Al-Qur’an yang hanya dikaji oleh kalangan terpelajar. Artikel ini akan mengungkap proses kepenulisan teks terjemah yang dikarang di era pra-kemerdekaan tersebut. Lebih jauh akan ditelaah faktor-faktor penyebab konten teks disusun dengan cara tertentu sebagai jawaban atau perlawanan atas permasalahan pada tempo itu. Teori hermeneutika Schleiermacher akan digunakan sebagai pendekatan untuk memahami gambaran keseluruhan atau nomena dan gambaran parsial atau fenomena dari teks. Dari sini ditemukan bahwa penulisan kitab ini dilakukan secara hati-hati karena adanya pengawasan dari pemerintah kolonial terhadap teks yang melawan status quo. Di samping itu nuansa kepesantrenan dan etika Jawa sangat kental memengaruhi gaya kepenulisan kitab.Kata Kunci: Terjemah, Hidāyah al-Raḥmān, kolonial, hermeneutika.